Financing health system elements in Africa: A scoping review. - Humphrey Cyprian Karamagi; David Njuguna; Solyana Ngusbrhan Kidane; Herve Djossou; Hillary Kipchumba Kipruto; Aminata Binetou-Wahebine Seydi; Juliet Nabyonga-Orem; Diane Karenzi Muhongerwa; Kingsley Addai Frimpong; Benjamin Musembi Nganda (PLoS ONE, 2023)
Countries that are reforming their health systems to progress towards Universal Health Coverage (UHC) need to consider total resource requirements over the long term to plan for the implementation and sustainable financing of UHC. However, there is a lack of detailed conceptualization as to how the current health financing mechanisms interplay across health system elements. Thus, we aimed to generate evidence on how to utilize resources from different sources of funds in Africa. We conducted a scoping review of empirical research following the six-stage methodological framework for Scoping Review by Arksey & O'Malley and Levac, Colquhoun & O'Brien. We searched for published and grey literature in Medline, Cochrane Library, PubMed, WHO database, World bank and Google Scholar search engines databases and summarized data using a narrative approach, involving thematic syntheses and descriptive statistics. We included 156 studies out of 1,168 studies among which 13% were conceptual studies while 87% were empirical studies. These selected studies focused on the financing of the 13 health system elements. About 45% focused on service delivery, 13% on human resources, 5% on medical products, and 3% on infrastructure and governance. Studies reporting multiple health system elements were 8%, while health financing assessment frameworks was 23%. The publication years ranged from 1975 to 2021. While public sources were the most dominant form of financing, global documentation of health expenditure does not track funding on all the health system dimensions that informed the conceptual framework of this scoping review. There is a need to advocate for expenditure tracking for health systems, including intangibles. Further analysis would inform the development of a framework for assessing financing sources for health system elements based on efficiency, feasibility, sustainability, equity, and displacement.